2019
DOI: 10.3390/molecules24030634
|View full text |Cite
|
Sign up to set email alerts
|

Onion (Allium cepa L.) Skin: A Rich Resource of Biomolecules for the Sustainable Production of Colored Biofunctional Textiles

Abstract: The aqueous extract of dry onion skin waste from the ‘Dorata di Parma’ cultivar was tested as a new source of biomolecules for the production of colored and biofunctional wool yarns, through environmentally friendly dyeing procedures. Specific attention was paid to the antioxidant and UV protection properties of the resulting textiles. On the basis of spectrophotometric and mass spectrometry analyses, the obtained deep red-brown color was assigned to quercetin and its glycoside derivatives. The Folin–Ciocalteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…The percentage of PerCP-eFluor 710 positive apoptotic cells was determined by flow cytometry [53,54]. The cells, after treatment, were collected by centrifugation, washed with PBS, stained with Fixable Viability Dye eFluor â 780 (eBioscience, CA) for 30 min and then washed with PBS and Flow Cytometry Staining Buffer.…”
Section: Apoptosis Analysismentioning
confidence: 99%
“…The percentage of PerCP-eFluor 710 positive apoptotic cells was determined by flow cytometry [53,54]. The cells, after treatment, were collected by centrifugation, washed with PBS, stained with Fixable Viability Dye eFluor â 780 (eBioscience, CA) for 30 min and then washed with PBS and Flow Cytometry Staining Buffer.…”
Section: Apoptosis Analysismentioning
confidence: 99%
“…Phenolic compounds such as gallic acid, catechin, and epicatechin are notoriously endowed with antioxidants, astringents, and antimicrobial activity. Therefore, such species are subject of increasing interest in various fields such as pharmaceuticals, leather tanning, cosmetics, and the food industry [7][8][9][10][11]. Low-molecular-weight hydroxybenzoic acids and some of their derivatives can be obtained from wood extractives and via induced lignin degradation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that YOPE contains considerable amount of quercetin as a major polyphenol. Other studies also reported the presence of quercetin in YOPE (Jeong et al, 2009;Pucciarini et al, 2019). Additionally, the TPC and TFC of YOPE in the films containing YOPE were determined (Table 3).…”
Section: Antioxidant Activitiesmentioning
confidence: 86%